Religion and Science in Dialogue: An Asian Christian View - Kim, Seung Chul (Zygon, 2016)
We may understand natural science as part of the attempt by human beings to understand themselves and their place in the world in which they find themselves. In this sense, as Karl Rahner has suggested, natural science flows naturally into anthropology. Consciously or unconsciously, science is always part of the drive to self-understanding. In an age of religious pluralism like ours, Christian faith in Asia is also brought face to face with the living reality of other religions, and that, too, cannot but affect how we understand our shared humanity.